Revising the SES: A Collaborative Process to Improve Assessment of Sexual Aggression and Victimization - White, Jacquelyn W. (Psychology of women quarterly, 2007)
The Sexual Experiences Survey (SES) assesses victimization and perpetration of unwanted sexual experiences (e.g., Koss, Gidycz, & Wisniewski, 1987). Revised versions of the SES that resulted from the work of the SES Collaboration are now available. This article reviews weaknesses of the SES that were identified, strengths that were preserved, and methodological considerations in the measurement of unwanted sexual experiences that informed the revisions. The primary changes include: more behavioral specificity; conversion to gender neutrality; full crossing of unwanted acts and coercive tactics; and revised and updated wording for assessing consent, alcohol-related incidents, unwanted acts, and coercive tactics. For illustration, the full text of the revised victimization version and its scoring rules are provided. The article concludes with suggestions for future research. These suggestions aim to involve researchers in a coordinated agenda to develop data that clarify methodological questions and contribute to continued improvement in assessing sexual victimization and perpetration